High-order hybrid DG-FV framework for compressible multi-fluid problems on unstructured meshes - Maltsev, Vadim; Skote, Martin; Tsoutsanis, Panagiotis (Elsevier, 2024)
In this work we extend the hybrid Discontinuous Galerkin/ Finite Volume framework, introduced in V. Maltsev, D. Yuan, K. W. Jenkins, M. Skote, P. Tsoutsanis, “Hybrid discontinuous Galerkin-finite volume techniques for compressible flows on unstructured meshes, Journal of Computational Physics 473 (2023)” [1], to multi-species problems involving gas-gas and gas-liquid systems. The numerical scheme achieves high order accuracy in smooth flow regions thanks to the DG discretisation, yet avoiding oscillations at material interfaces and shocks thanks to a FV type reconstruction. This strategy, as typically represented in literature, makes use of the so-called troubled cell indicators for the detection of numerical oscillations generated by an unlimited high-order scheme in presence of discontinuities, and enables a more dissipative scheme in the troubled cells only in order to suppress the spurious oscillations. As will be shown in a series of increasingly challenging test-cases, when applied to multi-species flows in the context of diffuse-interface models, the hybrid framework is able to limit the excessive material interface dissipation, characteristic of these interface-capturing methods, allowing at the same time a control over the amount of dissipation necessary to solve stiffer problems.
Keywords: High-order finite volume; Discontinuous-Galerkin; Shock-capturing; Multi-species flows; Diffuse-interface